Workplace aggression in organizational changing processes: The mediation role of leader political (soft and hard) behavior - Miranda, Sandra (2015)
One of the main trends in workplace aggression research is studying its antecedents. But the literature also reveals that some predictors remain understudied, like organizational change [1]. Additionally, possible mediators of this relationship were not investigated. The main objective of this research is studding the mediating effect of the leader political behavior (soft and hard version) on the relationship between organizational change and workplace aggression. Participants representing a wide variety of jobs across many organizations were surveyed. The measures used in this research are an Organizational Change Questionnaire climate of change, processes, and readiness [2], a Workplace Aggression Scale [e.g. 3, 4] and a Political Behavior Questionnaire [5]. The results of the study and its theoretical and practical implications will be presented and discussed.